Conjuring Life: Magic in the Poetics of Marina Tsvetaeva - Lane, Tora (Poznańskie Studia Slawistyczne, 2013)
This article discusses the notion of magic in the poetics of Marina Tsvetaeva (1892–1941) against the backdrop of romanticism and Russian modernism. Magic is related to the poet’s explorations of folklore, and also to Romantic, symbolist and futurist invocations of it. Concepts of magic are central to Tsvetaeva’s poetics; she considers conjuration to be a property of language that facilitates contact with the demonic, elemental and natural aspects of the world. These elemental aspects are not to be considered merely as the poet’s mythologisations of the world, but also as her reflections on the capacity of poetic language to speak of what is otherwise hidden in the world.